Bilateral Kienböck’s disease with bilateral negative ulnar variance: a case report - Sekej, Marjan; Rupreht, Mitja (Acta Medico-Biotechnica, 2021)
Purpose: Kienböck’s disease usually occurs unilaterally on dominant hands. As such, bilateral avascular necrosis of the lunate, in concurrence with bilateral negative ulnar variance (NUV), is a very rarely described condition. Case report: The case of a patient diagnosed with bilateral avascular necrosis of the lunate is presented. Plain film and magnetic resonance imaging confirmed bilateral NUV was also present. Conclusions: Although the relationship between Kienböck’s disease and NUV remains unclear, the bilateral concurrent appearance of both might instigate a discussion of the possible etiology of avascular lunate necrosis.